Association of long term sodium valproate monotherapy and vitamin D3 levels in epileptic children - Anum Shah, Imran Mahmood Khan, Sajid Hussain Sherazi, Taniah Ashfaq, Sajid Hussain Shah, Anum Shah, Imran Mahmood Khan, Sajid Hussain Sherazi, Taniah Ashfaq, Sajid Hussain Shah (Journal of Rawalpindi Medical College, 2021)
Objective: To determine the association of long term sodium valproate monotherapy and vitamin D3 levels in epileptic children Methods: This cross-sectional study was conducted in the Department of Pediatrics, Children Hospital, Pakistan Institute of Medical Sciences, Islamabad for six months from 15th February 2019 to 14th August 2019. A total of one hundred and thirty (n=130) children and adolescents of either gender between age 3-18 years who had a history of two seizures at least 24 hours apart in their life and were on sodium valproate monotherapy for more than one year were enrolled in this study through non-probability, consecutive sampling. Serum vitamin D3 (25-hydroxy vitamin D) levels were measured in all the patients at the time of enrolment into the study. All the demographic data and laboratory investigations were entered on the predesigned proforma and analyzed through SPSS version 17. Results: Vitamin D3 deficiency was found in 47 (36.2%) children which were significantly higher among patients with older age and longer duration of treatment (P<0.05) while gender and BMI of the patients did not show any significant difference (P>0.05). Conclusion: Significant percentage of epileptic children on sodium valproate monotherapy was found to have vitamin D3 deficiency. Therefore we recommend routine screening of vitamin D3 deficiency in all the epileptic children on long-term sodium valproate therapy followed by vitamin D supplementation in deficient patients.